IMPLEMENTASI POJOK BACA DI DESA JAEE PAGAR AIR: UPAYA MENINGKATKAN LITERASI DINI - Rifda, Rifda; Fatiya, Ulya; Azilla, Silvia; faridy, Faizatul (Kreasi: Jurnal Pengabdian Masyarakat, 2024)
The purpose of this community service program is to improve early literacy skills among children in Desa Ajee Pagar Air by implementing a reading corner (pojok baca). The background of this service lies in the low literacy rates among children in rural areas, which can be addressed by providing accessible resources and creating a conducive environment for reading. The service method used in this program is Participatory Action Research (PAR), which involves the active participation of the community in the planning and implementation process. The results show significant improvement in children's interest in reading and a positive shift in their literacy levels. The program contributed to fostering a culture of reading and learning, which will be sustained through continuous community involvement. In conclusion, the establishment of a reading corner in Desa Ajee Pagar Air has been successful in enhancing early literacy and promoting educational development in the community.